Generosity as a Constitutive Element in African Customary Law: Some Thoughts on Muvhali v Lukhele (21/34140) [2022] ZAGPJHC 402 (18 July 2022) - Ntando Sindane (Potchefstroom Electronic Law Journal)
Over the last decade, courts have been called upon to adjudicate the validity of marriages under the auspices of the Recognition of Customary Marriages Act 120 of 1998. In Muvhali v Lukhele (21/34140) [2022] ZAGPJHC 402 (18 July 2022) the high court had to decide on the validity of a marriage, considering contested claims to the succession of a deceased estate. In this case note I discuss the court's findings with the background of its reasoning that the inception of African customary law is born a the spirit of generosity. In implied terms, the court asserted that generosity is a constitutive element of customary law, insisting that this must be reflected in how both facts and the law are interpreted where customary disputes are concerned. I briefly investigate the essence of "generosity", its historicity and the potential implications for customary law disputes, particularly those that have to do with customary marriages. The thesis of my argument is that the acceptance of an undefined generosity as a constitutive element of customary law brings about a level of legal uncertainty, but that this is not a weakness. Instead, it is an opportunity for a radical (and even decolonial) re-imagination of a legal system that embraces the jurisprudence of generosity. If understood and applied correctly, African customary law can be exemplary for other disciplines of law in terms of achieving some of the transformative aspirations of the post-apartheid constitutional order.